2019
DOI: 10.1097/mlr.0000000000001067
|View full text |Cite
|
Sign up to set email alerts
|

How Much Does Medication Nonadherence Cost the Medicare Fee-for-Service Program?

Abstract: Background: Medication adherence is associated with lower health care utilization and savings in specific patient populations; however, few empirical estimates exist at the population level. Objective: The main objective of this study was to apply a data-driven approach to obtain population-level estimates of the impact of medication nonadherence among Medicare beneficiaries with chronic conditions. Research Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…However, adherence to these medications appears to be important for the long-term management of HF regardless of ejection fraction status [8]. Prior studies that have examined a subset of guideline-recommended medication categories have found that adherence is associated with improved outcomes, such as decreased risk for hospitalization [911], reduced healthcare costs [12, 13], and improved survival [9, 11, 14].…”
Section: Introductionmentioning
confidence: 99%
“…However, adherence to these medications appears to be important for the long-term management of HF regardless of ejection fraction status [8]. Prior studies that have examined a subset of guideline-recommended medication categories have found that adherence is associated with improved outcomes, such as decreased risk for hospitalization [911], reduced healthcare costs [12, 13], and improved survival [9, 11, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Nonadherence to chronic disease treatments is a significant issue. Lloyd et al estimated that, if 25% of Medicare beneficiaries with hypertension in the United States became adherent to an effective regimen, $13.7 billion could be saved annually by Medicare . Integrating pharmacists into the care management of chronic disease patients has demonstrated achievement of clinical outcomes and a positive return on investment, including in the community pharmacy …”
Section: The Time Is Now—making the Casementioning
confidence: 99%
“…Among older adults with epilepsy, the odds ratio of utilization of inpatient services was 0.66 among patients adherent to antiepileptic drugs compared with nonadherent patients and 13.2% less cost on the total direct health care costs [ 14 ]. Similarly, a population-level evaluation of the economic impact of nonadherence to medications used for the treatment of diabetes, heart failure, hyperlipidemia, and hypertension among Medicare beneficiaries in the United States demonstrated that improvement in adherence would result in an annual reduction of 117, 594 emergency department visits and over 7 million inpatient hospital days among patients with hypertension [ 15 ]. Likewise, reductions in these health care costs would also be realized in patients with hyperlipidemia, diabetes, and heart failure [ 15 ].…”
Section: Introductionmentioning
confidence: 99%